Reproductive Outcomes of Dual Trigger versus hCG Alone in Women Undergoing In Vitro Fertilization with Fresh Embryo Transfer Cycles - Fatma Ceren Guner; Murat Ozekinci; Ibrahim Inanc Mendilcioglu; Zeliha Kasabali (Obstetrics and Gynecology International)
Aim. To investigate the effect of the triggering method on the results of fresh embryo transfer in patients who underwent gonadotropin-releasing hormone antagonist cycles. Methods. The study was conducted retrospectively at a university-based tertiary reproductive center. The sample consisted of a total of 295 patients, of whom 111 were in the human chorionic gonadotropin (hCG) trigger group and 184 were in the dual trigger group. The main outcome measure of this study was the live birth rate, and secondary outcomes were the implantation rate, clinical pregnancy rate, miscarriage rate, and good-quality embryo rate. Results. Patient demographics and baseline characteristics did not significantly differ between the dual and hCG trigger groups. The results also indicated statistically nonsignificant differences between the two groups in terms of the number of oocytes retrieved (p>0.05), the number of mature oocytes (p>0.05), and the fertilization rate (p>0.05). The number of good-quality embryos (p=0.002) was higher in the dual trigger group compared with the hCG trigger group. However, the rates of clinical pregnancy and live births did not significantly differ between the groups (p>0.05). Conclusions. Although the number of total and high-quality embryos obtained was higher in the dual trigger group, there were no significant differences between the two groups in terms of pregnancy outcomes. The fresh embryo transfer yielded similar rates of implantation and live births in both trigger groups.